Determinants of Physicians' Brain Drain in Egypt - ElBeheiry, Mennatallah (AUC Knowledge Fountain, 2025)
Egypt is enduring a significant shortage of physicians, despite the annual graduation of approximately 10,000 medical students from its 27 medical schools. In 2016, the physician density was alarmingly low, with only one doctor per 12,285 people. This shortage is exacerbated by a physicians’ brain drain, as Egypt is a leading exporter of physicians to countries like the United Kingdom and Australia. As of 2020, the Egyptian Medical Syndicate reported 212,835 registered physicians, yet 56 percent of them work abroad, and only about 62,000 are actively employed in public hospitals, serving a population of over 110 million. The government’s efforts to address this shortage by increasing medical school admissions and expanding the number of medical schools are unlikely to be effective without deeper reforms. Additionally, as Egypt rolls out its Universal Health Insurance program, expected to be fully implemented by 2032, there is a pressing need for clear policies on the recruitment and retention of physicians to ensure the success of this initiative. Through employing an exploratory study that adopts a mixed methods approach, this study examines why and how the physicians’ brain drain phenomenon occurs. Theories and factors that affect the physicians' decision to migrate are explored to understand what pushes the Egyptian physicians out of Egypt, and what pulls them to their developed high-income country of interest. The study shows that poor healthcare facilities, unfavorable working conditions, low-quality training and limited educational opportunities, low remuneration, sociopolitical and economic issues in Egypt are the main factors that push Egyptian physicians out of Egypt. On the other hand, high-quality training and educational opportunities, well-developed health system, in addition to fair rewarding systems in the destination country are the main factors that pull Egyptian physicians to different high-income countries. Physicians’ brain drain is a rapidly expanding phenomena that negatively impacts the health system, the economy and society. This study can help policy makers understand why and how the physicians’ brain drain phenomenon occurs in Egypt, and hence make the right policy changes. Therefore, the study offers the following recommendations: updated nationwide database for human resources for health; reforming the medical training program; reforming the benefit package for physicians; reversing the brain drain through capitalizing on the returning physicians; and enabling future research to further investigate such expanding phenomenon.